A Moraxella Virulence Factor Catalyzes an Essential Esterase Reaction of Biotin Biosynthesis - Zeng, Qi; Yang, Qi; Jia, Jia; Bi, Hongkai (Frontiers in Microbiology, 2020)
Pimeloyl-acyl carrier protein (ACP) methyl ester esterase catalyzes the last biosynthetic step of the pimelate moiety of biotin, a key intermediate in biotin biosynthesis. The paradigm pimeloyl-ACP methyl ester esterase is the BioH protein of Escherichia coli that hydrolyses the ester bond of pimeloyl-ACP methyl ester. Biotin synthesis in E. coli also requires the function of the malonyl-ACP methyltransferase gene (bioC) to employ a methylation strategy to allow elongation of a temporarily disguised malonate moiety to a pimelate moiety by the fatty acid synthetic enzymes. However, bioinformatics analyses of the extant bacterial genomes showed that bioH is absent in many bioC-containing bacteria. The genome of the Gram-negative bacterium, Moraxella catarrhalis lacks a gene encoding a homologue of any of the six known pimeloyl-ACP methyl ester esterase isozymes suggesting that this organism encodes a novel pimeloyl-ACP methyl ester esterase isoform. We report that this is the case. The gene encoding the new isoform, called btsA, was isolated by complementation of an E. coli bioH deletion strain. The requirement of BtsA for the biotin biosynthesis in M. catarrhalis was confirmed by a biotin auxotrophic phenotype caused by deletion of btsA in vivo and a reconstituted in vitro desthiobiotin synthesis system. Purified BtsA was shown to cleave the physiological substrate pimeloyl-ACP methyl ester to pimeloyl-ACP by use of a Ser117-His254-Asp287 catalytic triad. The lack of sequence alignment with other isozymes together with phylogenetic analyses revealed BtsA as a new class of pimeloyl-ACP methyl ester esterase. The involvement of BtsA in M. catarrhalis virulence was confirmed by the defect of bacterial invasion to lung epithelial cells and survival within macrophages in the ΔbtsA strains. Identification of the new esterase gene btsA exclusive in Moraxella species that links biotin biosynthesis to bacterial virulence, can reveal a new valuable target for development of drugs against M. catarrhalis.